First record of the fruit fly, Diarrhegma modestum (Fabricius) (Diptera: Tephritidae) from Bangladesh (Bangladesh Journal of Zoology, 2015)
Abstract not availableBangladesh J. Zool. 41(2): 265-267, 2013